Effect of SP6 Acupressure on First-Period Labor Pain - Tanjung, Wiwi Wardani; Tetty Misbah; Eva Yusnita Nasution (PT Inovasi Pratama Internasional, 2023)
The process of labor begins with uterine contractions that cause pain and discomfort in laboring mothers. The main problem in laboring mothers is pain. Pain is a single sensation caused by a specific stimulus that is subjective and different for each individual. One of the non-pharmaceutical therapies for overcoming labor pain is acupressure. The aim is to determine the effect of SP6 acupressure on labor pain during the first stage at the Midwife Clinic Nelly M. Harahap Padangsidimpuan City. This study was conducted using a quasi-experimental research method (pseudo-experiment) using a Pretest posttest only design. The number of samples in this study was 20 respondents. sampling method using a purposive sampling technique. Data were analyzed univariately and bivariately. The results of the study found labor pain before the SP6 Acupressure action in laboring mothers at time I with a mean of 6.65 and after the SP6 Acupressure action in laboring mothers at time I with a mean value of 3.05. This study concludes that there is an effect of Acupressure SP6 on labor pain at time I with a p-value of 0.002. It is recommended that laboring women gain knowledge and experience in the implementation of Acupressure SP6 on labor pain at stage I.